Genotype-First Characterization of Familial Hypocalciuric Hypercalcemia Type 1: Prevalence, Serum Calcium and Clinical Associations - Nipith Charoenngam; Alicia Huerta-Chagoya; Sarah Hsu; Maheak Vora; Josep M Mercader; Miriam S Udler; Michael Mannstadt (Journal of Bone and Mineral Research, 2026)
Abstract Familial hypocalciuric hypercalcemia type 1 (FHH1), caused by inactivating CASR variants, is characterized by lifelong hypercalcemia and hypocalciuria and should be distinguished from primary hyperparathyroidism as their management differs substantially. Prior reports suggest additional clinical associations (e.g., pancreatitis, altered glucose metabolism), but epidemiological evidence is limited. Using a genotype-first analysis of UK Biobank (UKB) whole-exome/whole-genome sequencing data linked to health records, we estimated the prevalence of FHH1 and characterized its degree of hypercalcemia and clinical associations. Candidate variants were identified from the CASRdb database, which aggregates CASR variants reported in the literature and ClinVar/LOVD, and were supplemented with additional predicted high-impact variants. Variants were classified as FHH1-associated if designated in ClinVar as pathogenic/likely pathogenic (P/LP) or, for non-P/LP variants, determined to have high probability of causing FHH1 based on criteria that considered variant type, allele frequency and carrier serum calcium. We compared serum biochemistry with the remaining UKB population and performed PheWAS across ICD-10 diagnoses. Among 454,787 exomes/490,640 genomes, we identified 162 individuals carrying FHH1-associated variants (33.0/100,000). Mean serum calcium was higher in FHH1 than in the remaining UKB population (10.4±0.6 vs 9.5±0.4 mg/dL; p=1.2×10-72) but overlapped from approximately 9.2–9.4 mg/dL upward. PheWAS signals were dominated by calcium/parathyroid-related traits; pancreatitis- or diabetes-related outcomes did not meet multiple-testing-corrected significance thresholds. Serum phosphorus was modestly lower in FHH1 individuals (3.3±0.5 vs 3.6±0.5 mg/dL; p=6.7×10-17). To estimate FHH1 prevalence based on allele frequency, we used gnomAD v4.1 and found that the prevalence (SE) was 31.2(2.0)/100,000 overall and varied by ancestry, ranging from 46.6(12.5)/100,000 in the Admixed American group to 13.5(9.6)/100,000 in the Ashkenazi Jewish group. Taken together, these data indicate that FHH1 is more common than previously appreciated and is characterized by variable degrees of hypercalcemia and modest hypophosphatemia, although biochemical characterization was limited by unavailable urinary calcium and parathyroid hormone data.